HARDINESS GENERASI BANGSA DALAM MENGHADAPI TANTANGAN TRANSFORMASI KEINDONESIAAN PERSPEKTIF TERJEMAH KITAB IDZATUNNASYI’IN - Widia Astuti widia; Mulia Sari (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2024)
This study aims to explore the hardiness of the book Idzatunnasyi'in by al-Ghalayn and to find out its implementation in facing the challenges of the ongoing transformation of Indonesia. This is a qualitative study in the form of a literature study with primary data sources from the book Idzatunnasyi'in by al-Ghalayn and secondary data sources from several related articles and books. Hardiness in the book Idzatunnasyi'in has several concepts of mental or self-resilience such as hope, simplicity, effort and resignation, and self-confidence. The hardiness explained in the Book Idzotunnasyiin aims to shape character, how a person should behave when facing various events that happen to him or his nation in various fields. As well as forming a civilized, moral character that upholds the truth so that the Indonesian state continues to exist amidst these challenges.